Pemberian Inhalasi Minyak Kayu Putih Untuk Memperbaiki Pola Napas Tidak Efektif Pada Anak Dengan Bronkitis - SI PUTRI RAGIL; Murniati Murniati; Etika Dewi Cahyaningrum (LPPM UNIKAL, 2023)
There are 1.6 million persons who have bronchitis in Indonesia. Coughing, wheezing, sputum buildup, and shortness of breath are common symptoms. We must be mindful of the efficiency of breathing patterns when considering these symptoms. The goal of this study was to identify inefficient breathing techniques used by nurses to provide bronchitis-stricken An. A with nursing care. An. A is the focus of this case study in a scientific journal, and the study's findings include cough and runny nose, RR 32 beats per minute, additional rhonchi noises, SPO2 92%, body temperature 36.8 oC, and pulse 100 beats per minute. Airway control using eucalyptus oil inhalation was the intervention that was used. The major treatment for An's respiratory pattern issues was a straightforward inhalation of eucalyptus oil, and the findings of the case study were achieved following nursing care for airway management for three consecutive days. Increased inspiratory pressure, moderately decreased dyspnea, moderately decreased use of accessory muscles, decreased orthopnea, moderately decreased nasal breathing, improved respiratory rate, and improved respiratory depth are all signs that A can be substantially resolved. This demonstrates how eucalyptus oil can help bronchitis patients breathe more easily.Keyword: children, bronchitis, ineffective breathing pattern, simple inhalation